Mother-Tongue Interference in Learning English in English Meeting Club - Rahayu; Nurfajriah Basri (FOSTER: Journal of English Language Teaching, 2021)
Interference is a phenomenon that occurs in a society when learning a new language and bilingualism is one of the causes why interference is. Interference occurs mostly because the speakers who have more than one language used to interact with one another. This study aimed to describe the kind of interference errors made by learners of English in English Meeting of disorders caused by the mother tongue. This study used qualitative method which its subject was taken from participants of English Meeting. The collecting of data used audio recording which was converted into transcription. The results showed that interference errors committed by English language learners' is generally influenced to phonetic refers to speech sounds, lexical interference to the level of words and grammar disorder refers to the rules of grammar in language. This is due to the fact that the speaker Indonesia experienced a huge obstacle when trying to use English as the target language as first language learners have mastered. The source of the difficulties is based on the level difference between the Indonesian system and the English systemKeywords – Interference, Bilingualism, Interference errors